Using of Comic-Based Supplementary Material in Enhancing Studentsâ€™ Engagement and Food Preservation Competencies - Joyce Ann De Guzman; Edilberto Z. Andal, EdD (MASI Mandiri Edukasi, 2023)
The study assessed the relationship between studentsâ€™ engagement and Grade 6 Food Processing students' competencies concerning their perception of the comic-based supplementary material. Technology and Livelihood Education (TLE) has minimal studies about such concepts, so further research is needed. Â A description-correlation research method involving 30 Grade 6 students and a researcher-made questionnaire was utilized in data gathering. The findings revealed that the comic material was positively recognized by the students with an overall mean of 4.76 with a verbal interpretation of â€œstrongly agree,â€ while the overall mean of perceived student engagement after using the instructional material was 4.72, with the category